Exploring the evolving function of soluble intercellular adhesion molecule-1 in junction dynamics during spermatogenesis - Xiao, Xiang; Han, Yating; Li, Qin; Zheng, Dongwang; Cheng, C. Yan; Ni, Ya (Frontiers in Endocrinology, 2024)
Intercellular adhesion molecule-1 (ICAM-1) is a transmembrane glycoprotein expressed on immune, endothelial, and epithelial cells. Its ectodomain can be proteolytically cleaved to release a circulating soluble form called sICAM-1. Clinical studies demonstrate sICAM-1 is upregulated in various diseases and associated with disease severity. Research has identified sICAM-1 as a regulator of the blood-testis barrier (BTB) and spermatogenesis. Overexpression of sICAM-1 weakened the BTB in vitro and in vivo, downregulated junction proteins including N-cadherin, γ-catenin, and connexin 43, and caused germ cell loss. This contrasts with barrier-strengthening effects of membrane-bound ICAM-1. sICAM-1 may act as a molecular switch enabling germ cells to open BTB and Sertoli-germ cell adhesion for transport across the seminiferous epithelium. While the mechanism remains unclear, reduced SRC family kinase (SFK) signaling was observed following sICAM-1 overexpression. SRC promotes BTB protein endocytosis and degradation, influences cytoskeletal dynamics, and affects cell polarity. As sICAM-1 overexpression phenocopies SRC inhibition, SRC may operate downstream of sICAM-1 in regulating BTB dynamics and spermatogenesis. Investigating sICAM-1’s structure-function regions and downstream targets will elucidate the molecular mechanisms of junction disruption. This knowledge could enable strategies targeting sICAM-1/SRC to modulate BTB permeability and treat male infertility or diseases involving endothelial/epithelial barrier dysfunction.